2021
DOI: 10.1007/s00122-021-03912-0
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic diversity, distribution and domestication history of the neglected GGAtAt genepool of wheat

Abstract: Key message We present a comprehensive survey of cytogenetic and genomic diversity of the GGAtAt genepool of wheat, thereby unlocking these plant genetic resources for wheat improvement. Abstract Wheat yields are stagnating around the world and new sources of genes for resistance or tolerances to abiotic traits are required. In this context, the tetraploid wheat wild relatives are among the key candidates for wheat improvement. Despite its potential huge v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 101 publications
(160 reference statements)
0
20
0
Order By: Relevance
“…and the much more widespread prehistoric 'New Glume Wheat' (T. timopheevii s.l. ), of which the oldest archaeobotanical records were found in Turkey, has been intensively discussed in Badaeva et al [119].…”
Section: Evolution and Domestication Historymentioning
confidence: 99%
See 3 more Smart Citations
“…and the much more widespread prehistoric 'New Glume Wheat' (T. timopheevii s.l. ), of which the oldest archaeobotanical records were found in Turkey, has been intensively discussed in Badaeva et al [119].…”
Section: Evolution and Domestication Historymentioning
confidence: 99%
“…The tetraploid T. araraticum, the wild progenitor of the Timopheevii wheat lineage, potentially originated in Northern Iraq [101,117,118]. Based on analyses of nuclear and cytoplasmic genomes, T. araraticum can be divided into two subgroups: one subgroup (ARA-0) is widespread, while the other (ARA-1) is found only in South-eastern Turkey and North-western Syria [119]. Triticum timopheevii (2n = 4x = 28, GGA t A t ), the domesticated form of T. araraticum, has been cultivated only in western Georgia in the recent past.…”
Section: Evolution and Domestication Historymentioning
confidence: 99%
See 2 more Smart Citations
“…A number of authors have also reported different accessions of T. timopheevii as carrying karyotype rearrangements (Badaeva et al, 1994; Badaeva et al, 1990; Badaeva et al, 2022; Kawahara and Tanaka 1977; Taketa and Kawahara 1996). Thus, in addition to the species-specific translocations described above, the accession used in this work may have carried additional rearrangements affecting recombination and hence introgression.…”
Section: Discussionmentioning
confidence: 99%